How does the market view interests in jointly controlled entities? - Lourenço, I.; Fernandes, S.; Curto, J. (Revista Española de Financiación y Contabilidad - Spanish Journal of Finance and Accounting, 2012)
This study addresses whether the market views the venturer's share of the assets and liabilities of Jointly Controlled Entities (JCEs) as assets and liabilities of the venturer. The role of JCEs' assets and liabilities is a key question underlying the international debate on the appropriate reporting method for interests in JCEs. We estimate a cross-sectional valuation model based on that used in Landsman et al. (2008). Our valuation model is one that includes measures of the venturer's assets, liabilities and net income as well as measures of the venturer's share of JCEs' assets and liabilities. Findings are based on comparisons of assets and liabilities coefficients. They suggest that investors view the venturer's share of JCEs' assets and liabilities similarly to the assets and liabilities of the venturer. The findings thus provide some tentative support against the IASB's decision to eliminate proportionate consolidation from IAS 31.